World's Fair Music Hall, New York World's Fair 1939 (Grinnell Litho Co.)
Demonstrating a new form in theatre construction, the Hall of Music uses the flowing lines of functional construction throughout. Two and a half thousand spectators daily fill its auditorium ot hear and see many of the great musical presentations of our times.